2019
DOI: 10.11646/phytotaxa.424.4.5
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong><em>Trechispora yunnanensis</em></strong><strong> <em>sp. nov.</em> (Hydnodontaceae, Basidiomycota) from China</strong></p>

Abstract: A new wood-inhabiting fungal species, Trechispora yunnanensis sp. nov., is proposed based on morphological characteristics and molecular phylogenetic analyses. The species is characterized by resupinate basidiomata, rigid and fragile up on drying, cream to pale greyish hymenial surface; a monomitic hyphal system with generative hyphae bearing clamp connections, IKI-, CB-; ellipsoid, hyaline, thick-walled, ornamented, IKI-, CB-basidiospores measuring as 7-8.5 × 5-5.5 μm. The internal transcribed spacer (ITS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Currently, eight species of Trechispora have been reported from China (Dai, 2011;Xu et al, 2019), Trechispora alnicola, Trechispora cohaerens, T. farinacea, T. microspora, T. nivea, Trechispora polygonospora Ryvarden, Trechispora subsphaerospora (Litsch.) Liberta, and T. yunnanensis, and one species of T. yunnanensis was found in Yunnan Province of China and it differs from three new species by having a smooth to farinaceous hymenial surface and larger basidiospores (7-8.5 × 5-5.5 µm; Xu et al, 2019). Three new taxa do not closely group together in phylogenetic trees, and morphologically, T. bambusicola differs from T. fimbriata and T. fissurata by having granulose basidiomata with cream to buff hymenial surface and growth on dead bamboo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, eight species of Trechispora have been reported from China (Dai, 2011;Xu et al, 2019), Trechispora alnicola, Trechispora cohaerens, T. farinacea, T. microspora, T. nivea, Trechispora polygonospora Ryvarden, Trechispora subsphaerospora (Litsch.) Liberta, and T. yunnanensis, and one species of T. yunnanensis was found in Yunnan Province of China and it differs from three new species by having a smooth to farinaceous hymenial surface and larger basidiospores (7-8.5 × 5-5.5 µm; Xu et al, 2019). Three new taxa do not closely group together in phylogenetic trees, and morphologically, T. bambusicola differs from T. fimbriata and T. fissurata by having granulose basidiomata with cream to buff hymenial surface and growth on dead bamboo.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by the resupinate to effused basidiomata with smooth to hydnoid to poroid hymenophore, a monomitic or dimitic hyphal structure with clamped generative hyphae having typical ampullaceous septa, and short cylindric basidia and smooth to verrucose or aculeate basidiospores (Karsten, 1890;Bernicchia and Gorjón, 2010). About 49 species are currently known in Trechispora worldwide (Liberta, 1966(Liberta, , 1973Larsson, 1994Larsson, , 1995Larsson, , 1996Ryvarden, 2002;Trichiès and Schultheis, 2002;Miettinen and Larsson, 2006;Ordynets et al, 2015;Xu et al, 2019) and Index Fungorum 1 and MycoBank 2 . Larsson (2007) addressed the classification of corticioid fungi and revealed that Trechispora farinacea (Pers.)…”
Section: Introductionmentioning
confidence: 99%
“…However, morphologically T. xantha differs from T. daweishanensis by having a smooth hymenophore that cracks, and a buff hymenial surface in contrast to T. daweishanensis which has a white (at least when fresh) tuberculate hymenial surface and the presence of larger crystals among subiculum and subhymenium. Trechispora yunnanensis differs in having thick-walled, ornamented and larger basidiospores (7-8.5 × 5-5.5 μm, Xu et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Liberta (1973Liberta ( : 1878. Based on the ITS+nLSU dataset, Xu et al (2019) introduced a new taxon, T. yunnanensis C.L. Zhao (2019: 256) within Trechispora, which formed a monophyletic lineage and was closely related to T. byssinella (Bourdot) Liberta (1966: 318) and T. laevis K.H.…”
Section: Introductionmentioning
confidence: 99%
“…Tricholomataceae are primarily soil saprophytes, and they are members of the CHEGD (the acronym of the constituent taxa: Clavariaceae, Hygrophoraceae, Entolomataceae, Geoglossaceae and Dermoloma) symbiotic fungi [38,39]. The Hydnodontaceae are woody saprophytes [40].…”
Section: Ecological Functions Of Dominant Fungi In Microhabitatsmentioning
confidence: 99%